Efforts to increase nutritional status among Cytomegalovirus (CMV) infected children - Iroma Maulida; Ratih Sakti Prastiwi; Umriaty Umriaty (International Journal of Public Health Science (IJPHS), 2020)
Malnutrition has an interrelated relationship with infectious diseases, where infection can occur malnutrition and can cause malnutrition in children. Children who infected with CMV need an increase in nutritional status, but with malnutrition, the recovery process and the body's immune enhancement cannot be optimal. This study aimed to identify the efforts to improve the nutritional status of children infected with CMV in Tegal, Central Java, Indonesia. This study was a qualitative study with phenomenological approach. The informants were parents or caregivers of the children infected with CMV. Data obtained through interviews and observations, which then analyzed through the stages of data reduction-presentation-drawing conclusions. Data were analyzed using triangulation methods. The results showed that the nutritional status of children after recovery of CMV infection had increased. That was because the informant always ensures nutrients needed even given using a soft texture and gradually increase to rough. The tendency of informants to provide the same food has the risk of increasing the deficiency of micronutrients in children. Therefore we need an effort to improve the provision of food variations in children.